Relation between vesical function and gait in people with human T-Lymphotropic virus type 1 - Silva, Nayara Morais Magno e (2018)
Current analytic, observational and transversal study correlates bladder dysfunction and the need for gait aid in people with human T-lymphotropic virus type 1. Investigation was undertaken with 16 patients of both genders, with a definite diagnosis for Tropical Spastic Paraparesis/Mielopathy, associated with HTLV-1 (PET/MAH), evaluated by the Spastic Paraplegia Rating Scale (SPRS) and characterized as to help degree in gait by devices employed during walking. Finding were codified by the International Classification for Functionality, Disability and Health (ICF). Findings related to vesical function were converted into component body functions; in the case of gait aid, they were converted into activity and participation. G test (adherence), chi-square and Spearman´s correlation for statistical analysis (p≤0.05) were employed. Most patients had a slight condition for vesical function (b6202.1), with no (d465.0) or only moderate difficulty (d465.2) for gait aid. There was a correlation (p=0.009) between gait aid and bladder function. ICF codes revealed that the greatest the difficulty in locomotion, the biggest the issue in bladder function.